An Alteration in the Cecal Microbiota Composition by Feeding of 1-Kestose Results in a Marked Increase in the Cecal Butyrate Content in Rats - Tochio, Takumi (PLoS One, 2016)
Functional food ingredients, including prebiotics, have been ardently developed for improving the intestinal environment. Fructooligosaccarides (FOS), including fructans, are the well researched and commercialized prebiotics. However, to our knowledge, few studies have been conducted on the physiological effects of each component of FOS as prebiotics. 1-Kestose, a component of FOS, is composed of one glucose and two fructose molecules, and is considered as a key prebiotic component in short-chain FOS. In the present study, we examined the effects of dietary 1-kestose using 0.5–5% 1-kestose diets on cecal microbiota composition and cecal contents of short-chain fatty acids and lactate in rats. The findings indicate that dietary 1-kestose induced cecal hypertrophy and alterations in the cecal microbiota composition, including a marked increase in the cell number of Bifidobacterium spp. These alterations were associated with significant increases in acetate and lactate, and a marked increase in butyrate in cecal contents. Furthermore, dietary 1-kestose induced a significant decrease in serum insulin concentration in rats fed 2.5–5% 1-kestose diet. These findings suggest a potential of 1-kestose to be a prebiotic for improving the metabolism of the host.